2015
DOI: 10.3233/pep-2012-014
|View full text |Cite
|
Sign up to set email alerts
|

Frontal lobe dysfunctions in patients with juvenile myoclonic epilepsy

Abstract: Juvenile myoclonic epilepsy (JME) is a common form of idiopathic generalized epilepsy. Behavioral and cognitive problems are frequently observed in JME. Although the underlying mechanisms are still unknown, recent neuropsychological and neuroimaging studies provide strong evidence for frontal lobe dysfunction. Neuropsychological studies have shown JME patients to be impaired in a number of executive functions such as concept formation, abstract reasoning, mental flexibility, and cognitive speed and planning. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 51 publications
(106 reference statements)
0
3
1
Order By: Relevance
“…Family history of epilepsy, age at onset of seizures, sex, presence of PPR, results of conventional magnetic resonance imaging (cMRI) and delayed diagnosis were not significantly associated with drug resistance as reported in some previous studies [15,16]. Contrary to our results, the true-resistant course was significantly associated with psychiatric disorders [14][15][16] and the presence of thyroid diseases [16]. Myoclonic jerks alone, without GTCS or absence seizures have been reported to occur in 7-17% of JME probands [1].…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Family history of epilepsy, age at onset of seizures, sex, presence of PPR, results of conventional magnetic resonance imaging (cMRI) and delayed diagnosis were not significantly associated with drug resistance as reported in some previous studies [15,16]. Contrary to our results, the true-resistant course was significantly associated with psychiatric disorders [14][15][16] and the presence of thyroid diseases [16]. Myoclonic jerks alone, without GTCS or absence seizures have been reported to occur in 7-17% of JME probands [1].…”
Section: Discussioncontrasting
confidence: 86%
“…It is usually assumed that continuous pharmacotherapy is required, although about 10% of them appear to have permanent remission in adolescence [13]. Discontinuing AED treatment in JME is very important for the long-term social outcome and quality of life of the patients and requires an individual risk assessment [9,14].…”
Section: Introductionmentioning
confidence: 99%
“…The results pertaining to both FAB and EXIT were in agreement with the previous studies reiterating the significant executive dysfunction in JME patients. [ 6 7 8 9 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…Various studies employing sensitive neuropsychological tests have demonstrated frontal lobe dysfunction in patients with JME. [ 6 7 8 9 ]…”
Section: Introductionmentioning
confidence: 99%